Comparison of VDR Expression and Blood Vitamin D 1.25 (OH)2 Level between Cervical Cancer Patients and Normal Women - Brahmana Askandar; Very Great Ekaputra; Teuku Mirza Iskandar (National Cancer Center - Dharmais Cancer Hospital, 2020)
Background: Vitamin D and its receptor (VDR) play a crucial role in the development of gynecological cancers. This study aims to evaluate the VDR expression and blood vitamin D 1.25 (OH)2 levels in cervical cancer patients and healthy women.Methods: This is a cross-sectional study. In vitro quantitative examination (ELISA) was used for the measurement of vitamin D 1.25 (OH)2 and Sandwich-ELISA was applied for quantitative determination in vitro concentration of Human VDR in serum.Results: The number of research subjects consisting of 20 cervical cancer patients based on clinical and histopathological results and 20 women without cervical cancer based on clinical and pap smear results. The mean vitamin D 1.25 (OH)2 levels in the cervical cancer group of 209.23 ± 71.476 pg/mL were significantly lower than in the group of normal women of 339.79 ± 139.003 pg/mL (P=.001). The mean VDR expression in the cervical cancer group of 5.38 ± 5.478 ng/mL was significantly higher than the group of normal women of 1.89 ± 1.657 ng/mL (P=.018). The best cut-off value for vitamin D levels is 239.25 pg/mL (sensitivity 70% and specificity 75%). The cut-off value for VDR expression is 2.23 ng/mL (sensitivity 60% and specificity 75%). Low vitamin D levels increase the risk of cervical cancer incidence by 2.7 times greater, and an increase in VDR expression increases the risk of cervical cancer incidence 2 times greater.Conclusions: The study results indicated a higher expression of VDR and lower levels of vitamin D 1.25 (OH)2 in cervical cancer compared to normal women. Low levels of vitamin D increase the risk of cervical cancer incidence by 2.7 times greater, and higher VDR expression increases the risk of cervical cancer incidence 2 times greater.